2023
DOI: 10.1002/prp2.1066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of different doses of ciprofol for induction of general anesthesia in elderly patients: A randomized, controlled trial

Abstract: Ciprofol is a newly developed intravenous anesthetic agent with improved pharmacokinetic properties. Compared to propofol, ciprofol exhibits stronger binding to the GABAA receptor and elicits a greater enhancement of GABAA receptor‐mediated neuronal currents in vitro. The aims of the present clinical trials were to examine the safety and efficacy of different doses of ciprofol for induction of general anesthesia in elderly patients. A total of 105 elderly patients undergoing elective surgery were randomized, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
2
6
1
Order By: Relevance
“…This study also found a signi cant difference in the ED50 of ciprofol for TB patients of different genders and ages, and the ED50 of ciprofol in elderly patients were signi cantly lower than the non-elderly patients, and ED50 of ciprofol in the female patients were signi cantly lower than the male patients, suggesting that there may be age and gender differences in the pharmacokinetics and pharmacodynamics of ciprofol, which was consistent with Li et al's conclusion that the use of 0.3 mg/kg of ciprofol in elderly people was equally effective as the use of 0.4 mg/kg in non-elderly people [10]. It was also consistent with the conclusion reported by Duan et al that the recommended use of low-dose (0.3 mg/kg) ciprofol for anesthesia induction in elderly patients had better safety and effectiveness [11], which may be related to weakened liver and kidney functions and cardiovascular system decline in the elderly [15,25]. Elderly patients have a decrease in myocardial contractility, coronary blood ow, and ventricular compliance, making it di cult for them to tolerate excessive volume loading [26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study also found a signi cant difference in the ED50 of ciprofol for TB patients of different genders and ages, and the ED50 of ciprofol in elderly patients were signi cantly lower than the non-elderly patients, and ED50 of ciprofol in the female patients were signi cantly lower than the male patients, suggesting that there may be age and gender differences in the pharmacokinetics and pharmacodynamics of ciprofol, which was consistent with Li et al's conclusion that the use of 0.3 mg/kg of ciprofol in elderly people was equally effective as the use of 0.4 mg/kg in non-elderly people [10]. It was also consistent with the conclusion reported by Duan et al that the recommended use of low-dose (0.3 mg/kg) ciprofol for anesthesia induction in elderly patients had better safety and effectiveness [11], which may be related to weakened liver and kidney functions and cardiovascular system decline in the elderly [15,25]. Elderly patients have a decrease in myocardial contractility, coronary blood ow, and ventricular compliance, making it di cult for them to tolerate excessive volume loading [26].…”
Section: Discussionsupporting
confidence: 90%
“…The age of the non-elderly group was de ned as 18-64 years old, while the age of the elderly group was de ned as ≥ 65 years old [10,11]. The exclusion criteria were as follows: patients with recent major hemoptysis, severe stenosis of the main airway, myasthenia gravis, severe cardiovascular disease, longterm history of taking psychotropic drugs, allergies to anesthetic drugs and their components, and estimated surgical duration exceeding 30 minutes.…”
Section: Patients and Clinical Protocolmentioning
confidence: 99%
“…This aligns with effective doses reported in earlier phase I-III studies and provides a more precise estimation. Our study reveals a slightly higher effective dose of ciprofol compared to the 0.3 mg/kg recommended by Wu 15 , Ding 16 , and Duan 17 . This variation may be due to the different stimulation intensities between beroptic bronchoscopy and tracheal intubation, and the use of topical anesthesia in Wu's study prior to bronchoscope insertion.…”
Section: Discussioncontrasting
confidence: 55%
“…Though most studies affirm the safety of both drugs for clinical practice, it is worth noting that the existing literature on the comparison between these two drugs is relatively limited. Looking ahead, future research should delve into optimized ciprofol dosing strategies aimed at achieving the desired depth of anesthesia while minimizing side effects [ 33 ]. Exploring patient-centered outcomes and integrating advanced monitoring technologies could also provide deeper insights into the comparative strengths and weaknesses of these agents.…”
Section: Discussionmentioning
confidence: 99%